The Role Of Managerial Ownership In The Relationship Of Debt Policy To Shareholder Value In Financial Companies In Indonesia - Putri Regina Prayoga; Nikmah Nikmah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of debt policy on shareholder value with managerial ownership as a moderation variable. The research sample used financial companies listed on the Indonesia Stock Exchange during 2019-2022. The analysis method uses multiple regression tests and MRA (Moderator Regression Analysis) tests. The results of this study show that debt policy proxied by DAR has a positive effect on shareholder value, managerial ownership has a negative effect on shareholder value and managerial ownership is proven to moderate the relationship of debt policy to shareholder value. Debt policy proxied by DER has no effect on shareholder value, and managerial ownership also has no effect on debt policy.